Cultural Content Analysis of English Textbook Entitled When English Rings A Bell for Seventh Grade - Reynaldi, Kelvin (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
Language and culture are intertwined in a way that demonstrates how the circumstances, people involved, and prior experiences change over time. The cultures discussed in the textbook When English Rings a Bell are the focus of this investigation. A descriptive qualitative research design, specifically textbook content analysis, is used in this study. When English rang a bell, the Bahasa Inggris textbook featured source culture more than any other type of culture (61.74 percent). The fact that textbooks are more likely to encourage students to learn English from their own cultures was taken into consideration. Target culture came in second with a percentage of 38.26 percent, followed by international culture, which came in last with a percentage of 0%. The international culture was not mentioned in the chapters or on the pages. Even though the Ministry of National Education published the textbooks, the cultural content is not balanced. The textbook typically emphasizes local cultures when teaching English. It effectively educates students about their own cultures.